Growth of Religious Organizations during Indonesia's National Recovery Period - Ramadhani, Nadia; Adiputri, Cici; Febriani, Ira (Holistic Science, 2024)
This article aims to describe the role of Islamic social organizations (ormas) in the development of Indonesia. The method used in this paper is descriptive analysis. The results of the discussion indicate that Islamic organizations have played a role from the independence struggle to the present day. There are Islamic organizations in the era of independence, the old order, the new order, and the present day. Islamic organizations need to actively contribute to the development of Indonesia by acting as a link between community aspirations and the government. Additionally, Islamic organizations should enhance their role in deradicalization programs to prevent terrorist acts and radicalism.